Effect of Employee–Customer Interaction Quality on Customers’ Prohibitive Voice Behaviors: Mediating Roles of Customer Trust and Identification - Chen, Guofu; Li, Shuhao (Frontiers in Psychology, 2021)
Given that customer voice behaviors are confused with customer complaint behaviors in usage, this study thoroughly explains the essential differences between the two constructs. On that basis, this study investigates how employee–customer interaction (ECI) quality affects customers’ prohibitive voice behaviors, which is an crucial type of customer voice behaviors, by examining customer trust and identification as mediators. Data from 395 restaurant customers are collected and analyzed using structural equation modeling. Results show that ECI quality positively affects customers’ prohibitive voice behaviors. In this effect, customer trust and identification play direct and sequential mediating roles. This study contributes theoretically to the current knowledge by clearly distinguishing customer voice behaviors from customer complaint behaviors and by providing new insights into the mechanism of customers’ prohibitive voice behaviors from the perspectives of service interaction and relational benefit enhancement. The practical implications of this study can help pointedly foster customers’ prohibitive voice behaviors.